THE PROCEDURE FOR CREATING THE CONTENTS OF SCIENCES IN THE PLAN OF CALENDAR SCIENCES ON THE BASIS OF THE CURRICULUM (MODULE) OF SCIENCE WORK IN PROFESSIONAL EDUCATIONAL INSTITUTIONS - Muxiddin Farzona (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: In this paper, the reforms in the professional education system in Uzbekistan, its important issues and the concept of professional education are discussed. Also, the main requirements for the development of the Calendar subject plan were discussed.